The Low Voices: Quality, Ethics, and Reach of Qualitative Data* - Cuesta-Benjumea, Carmen de la (Investigación y Educación en Enfermería, 2023)
* Clarification. This article is based on the key-notespeech given by the author during the 9th Iberian-American Congress on Qualitative Research -Montevideo, Uruguay, 13-15 October 2021.